A development toolchain for a pulsed injector-ejector unit for PEM fuel cell applications. (1st July 2022) - Singer, Gerald; Gappmayer, Gregor; Macherhammer, Marie; Pertl, Patrick; Trattner, Alexander
Abstract: The anode subsystem of PEM fuel cells has to supply hydrogen in the required temperature, pressure, mass flow and concentration range under all operating conditions. At present, several components such as valves, sensors and a recirculation pump/blower (active recirculation) secure the supply, which consumes a significant amount of energy and reduces the overall efficiency. Passive recirculation with a pulsed injector-ejector unit is a promising approach to guarantee the required supply while maintaining low energy consumption. However, high development efforts are necessary to design and optimize an injector-ejector for the entire operating range. This paper proposes a novel development toolchain consisting of simulation models and experimental validation. In addition, simulation and measurement results are within a 2% accuracy for the stoichiometric ratio at nominal power. Further, the results show that recirculation covers the entire operating range. This toolchain enables accurate design and optimization of injector-ejector units saving development time and costs. Graphical abstract: Image 1 Highlights: Toolchain consists of base calculations, ejector and anode simulation, and testing. The appropriate tool can reduce time and costs in the current development phase. The higher the injector frequency, the lower the pressure fluctuations in the anode. N2 accumulation increases entrainment ratio and decreases stoichiometric ratio. Required stoichiometric ratio is covered for the operating range of the PEM FCS.